Digital Transformation in MSMEs: A Systematic Review of E- Commerce Implementation Challenges and Opportunities - Indah Aprilia Putri; Reni Shinta Dewi; Andi Wijayanto (International Journal of Economics, Business and Innovation Research, 2025)
The growing pressures of a knowledge-based economy have made digital transformation increasingly essential for Micro, Small, and Medium Enterprises (MSMEs). Responding to this need, the present study reviews existing literature on how MSMEs implement digital marketing and e-commerce, with attention to their strategic approaches, the obstacles they encounter, and the performance outcomes associated with digital adoption. Through a Systematic Literature Review (SLR) of fifteen peer-reviewed publications from 2020 to 2025—most of which examine MSMEs in developing nations, especially Indonesia—the study identifies clear benefits of digital tools in enhancing competitiveness, innovation, and organizational resilience. However, these gains depend heavily on adequate digital literacy, capable human resources, and institutional preparedness. Persistent challenges include financial limitations, weak technological understanding, and insufficient skills development, though government initiatives, training programs, and ecosystem collaborations offer partial solutions. Evidence from Bangladesh and Jordan further supports the view that e-commerce, when paired with innovation capacity and strategic orientation, can improve MSME performance beyond domestic markets. Overall, the review emphasizes that narrowing the digital divide requires more than simply adopting new technologies; it entails fostering an innovation mindset, aligning multi-sector policies, and ensuring sustained capacity building to strengthen MSME competitiveness in the digital era.